Footholds for pioneers: How geomorphic features accelerate early marsh assembly - Mingxuan Wu; Zhiyuan Zhao; Gregory Fivash; Jim van Belzen; Tjeerd J. Bouma; Yuxi Ma; Tim Grandjean; Xiaowei Ding; Roeland C. van de Vijsel; Johan van de Koppel (Limnology and Oceanography, 2026)
Ecosystem transitions from bare to vegetated states often stall at early stages, before the biogeomorphic feedbacks needed for further expansion take hold. In aquatic systems, this bottleneck is especially common where inundation and hydrodynamic conditions may impose strong abiotic filters on pioneer establishment. Here, we integrate a manipulative field experiment with a simple probabilistic model to test whether tidal creeks, ubiquitous geomorphic features in tidal flats, can help overcome this bottleneck during early marsh assembly. In plots adjacent to experimentally created tidal creeks, transplanted seedlings of the pioneer halophyte Tripolium pannonicum had ~ 20% higher survival, grew taller, and were ~ 50% more likely to flower within a single growing season than seedlings in no‐creek controls. Using the field‐derived survival and flowering differences to estimate potential local seed supply, model simulations predicted higher recruitment probability and a shorter expected time lag to recruitment. Together, our findings demonstrate that geomorphic features can provide local footholds for pioneers and thereby contribute to early marsh assembly. These results emphasize the need to include geomorphic heterogeneity as a design principle of restoration strategies, improving recruitment conditions before vegetation feedbacks become established.